Ambidexterity's influence on export strategy development—The case of the Indian pharmaceutical industry. (15th May 2022) - Kolte, Ashutosh; Festa, Giuseppe; Rossi, Matteo; Thrassou, Alkis; Vrontis, Demetris; Christofi, Michael
Abstract: This study investigates the influence that business ambidexterity of the Indian pharmaceutical industry can exert on exports, after the evolution from producer—often with the support of foreign direct investments (FDIs)—to researcher. The growth rate of the sector has changed pace with the introduction of new rules regarding patents, impelling pharma enterprises to invest in research and development (R&D), also for the peculiar category of AYUSH. However, many aspects of this industrial evolution are, if anything, under researched. To fill this gap in knowledge, this research adopts a quantitative methodology on secondary data to investigate the effects and potentialities of ambidexterity, providing evidence from descriptive and inferential statistics. Insisting on traditional production of generics (exploitation) and investing in R&D (exploration) have been coherent with the rise in exports, but several factors still impede the development of the commercial potential of the Indian pharmaceutical industry, mostly due to low per capita health care spending, absence of reliable infrastructure, and severe market competition.